Social inequality - Louise Warwick-Booth (Los Angeles, Calif. : Sage, 2019)
Accessible and engaging, the second edition of Social Inequality is your essential guide to social inequality and stratification. Covering key theories, ideologies and concepts, this book brings a complex social phenomenon to life with contemporary examples and learning features. Offering a nuanced analysis of the subject, this book includes: Two new chapters on Youth and Age, and Health and Disability; Updated coverage of sexuality and transgender issues; Discussions on migration and asylum seeking; A global context, offering a comparative discussion on social inequalities, policy, and justice. Lucidly written, this is a key companion that will enhance your understanding of the dynamics of social inequality--back cover
Keywords: Equality; Socioeconomic Factors; Healthcare Disparities